Recent methods in detection of olive oil adulteration: State-of- the-Art - Fataneh Hashempour-baltork; Somaye Vali Zade; Yeganeh Mazaheri; Adel Mirza Alizadeh; Hossein Rastegar; Ziba Abdian; Mohammadali Torbati; Sodeif Azadmard Damirchi (Journal of Agriculture and Food Research, 2024)
Olive oils have high consumption due to their health benefits and also owe higher economic value and a grwing demand in the market. However, blending lower grade oils with virgin olive oil can harm its nutritional value and market value. There are valuable reviews on the conventional methods on the detection of olive oils adulteration, but this review focuses on recent literatures on the detection this adulteration through advanced coupling analytical techniques, emphasizing the application of chemometrics in olive oil research.Recent studies have successfully improved the detection limit by combining different methods or modifying existing ones. Each technique has its own strengths and limitations, making them more suitable for specific types of adulteration. The integration of new and advanced detection methods, along with the use of chemometrics, was not found in earlier review research papers. NMR reveals the chemical composition and structure of the oils, while chromatography separates and identifies individual components. DNA-based methods detect genetic material, and electronic nose detects differences in odor or taste. In practice, a combination of multiple analytical techniques enhances the accuracy and reliability of detecting olive oil adulteration. Chemometrics, a mathematical and statistical approach to analyzing large datasets, helps interpret the results and identify patterns and trends that may indicate adulteration.